Optical absorption and photoluminescence studies of Dy3+: LCZSFB glasses - Madhukar Reddy, C.; R Dillip, G.; Mallikarjuna, K.; Sudhakar Reddy, B.; Vemasevana Raju, K.; Deva Prasad Raju, B. (Photonics Letters of Poland, 2011)
Lead containing calcium zinc sodium fluoroborate [LCZSFB] glasses doped with different Dy3+ ion concentrations have been prepared and characterized through optical absorption and photoluminescence studies. The three phenomenological intensity parameters W? (?=2,4 and 6) hav been determined from the absorption spectral intensities using the Judd-Ofelt (J-O) theory. The hypersensitivity of 6H15/2 ? 6F11/2 transition based on the magnitude of W2 paramete has also been discusse. By using the J-O intensity parameters several radiative properties such as spontaneous transition probabilities, radiative branching ratios and radiative lifetimes have been determined. The effect of Dy3+ ion concentration on emission intensities has also been reported and stimulated emission cross section of emission transitions is also reported. Full text: PDF References: G. Ajith Kumar, P.R. Biju, N.V. Unnikrishnan, "Absorption and emission properties of Nd3+ in lithium cesium mixed alkali borate glasses", Phys. Chem. Glasses. 40, 219 (1999). P. Santa-Cruz, D. Martin, J. Dexpert-Ghys, A. Sadoc, F. Glas, F. Auzel, "New lanthanide-doped fluoride-based vitreous materials for laser applications", J. Non-Cryst. Solids. 190, 238 (1995). [CrossRef] P. Egger, J. Hulliger, "Optical materials for short wavelength generation", Coord. Chem. Rev. 183, 101 (1999). [CrossRef] R. Ciceo-Lucacel, I. Ardelean, "FT-IR and Raman study of silver lead borate-based glasses", J. Non-Cryst. Solids 353, 2020 (2007). [CrossRef] A. Verabdra Rao, C. Laxmikanth, B. Apparao, N. Veeraiah, "Dielectric relaxation and a.c. conduction phenomena of PbO?PbF2?B2O3 glasses doped with FeO", J. Phys. Chem. Solids. 67, 2263 (2006). [CrossRef] P. Abdul Azeem, S. Balaji, R.R. Reddy, "Spectroscopic properties of Dy3+ ions in NaF-B2O3-Al2O3 glasses", Spectrochem. Acta Part A 69, 183 (2008) B.R. Judd, "Optical Absorption Intensities of Rare-Earth Ions", Phys. Rev. 127, 750 (1962). [CrossRef] G.S. Ofelt, "Intensities of Crystal Spectra of Rare-Earth Ions", J. Chem. Phys. 37, 511 (1962). [CrossRef] J. Suresh Kumar, K. Pavani, A. Mohan Babu, Neeraj Kumar Giri, S.B. Rai, L. Rama Moorthy, "Fluorescence characteristics of Dy3+ ions in calcium fluoroborate glasses", J. Lumin. 130, 1916 (2010). [CrossRef] B.C. Jamalaiah, J. Suresh Kumar, T. Suhasini, Kiwan Jang, Ho Sueb Lee, Hyukjoon Choi, L. Rama Moorthy, J. Alloys Compd. 474, 382 (2009) C.K. Jorgensen, B.R. Judd, "Hypersensitive pseudoquadrupole transitions in lanthanides", Mol. Phys. 8, 281 (1964). [CrossRef] S. Tanabe, T. Ohayagi, N. Soga, T. Hanada, "Compositional dependence of Judd-Ofelt parameters of Er3+ ions in alkali-metal borate glasses", Phys. Rev. B 46, 3305 (1992). [CrossRef] M.B. Saisudha, J. Ramakrishna, "Effect of host glass on the optical absorption properties of Nd3+, Sm3+, and Dy3+ in lead borate glasses", Phys. Rev. B 53, 6186 (1996). [CrossRef] C. Gorller-Walrand, K. Binnemans, Handbook on the Physics and Chemistry of Rare Earths (North-Holland, Amsterdam, 1998). C.K. Jorgensen, R. Reisfeld, "Judd-Ofelt parameters and chemical bonding", J. Less Common Met. 93, 107 (1983). [CrossRef] C.K. Jayasankar, E. Rukmini, "Spectroscopic investigations of Dy3+ ions in borosulphate glasses", Physica B 240, 273 (1997). [CrossRef] D.K. Sardar, W.M. Bradley, R.M.Yow, J.B. Gruber, B. Zandi, "Optical transitions and absorption intensities of Dy3+ (4f9) in YSGG laser host", J. Lumin. 106, 195 (2004). [CrossRef] P. Babu, C.K. Jayasankar, "Spectroscopic properties of Dy3+ ions in lithium borate and lithium fluoroborate glasses", Opt. Mater. 15, 65 (2000). [CrossRef]